Persepsi Akuntan Pendidik dan Praktisi terhadap Independensi Penampilan Akuntan Publik dan Advertensi Jasa Kantor Akuntan Publik (Survei di Surakarta dan Yogyakarta) - Nani Amani; Sulardi Sulardi (Jurnal Akuntansi dan Bisnis, 2005)
This study aims to identify factors that effect public accountants’s appearance. This study also aims to know weather there is a different perception of independence of appearance between educator accountant and practitioner. Investigation on 132 respondents from educator accountant and practitioner, found that all factor significant affecting independence of appearance of public accounting. The test also result there is no different perception of independence of appearance of public accountant between educator accountant and practitioner. Factors that test in this research are financial interest in the client’s company and bussiness relationship with their clients, non audit services, audit fee, competition in providing auditing service among auditors, the length of continuiting audit services, the size of the auditor firm, and the advertising of the audit firm.